Teacher–Student Relationships in EFL Classrooms: Insights into Students’ Engagement and Enjoyment from Teachers’ and Students’ Perception - Ni Putu Tasya Sukmapratiwi; Luh Putu Artini; Luh Indrayani (Journal of Educational Study, 2026)
Teacher–student relationship (TSR) has been recognized as an important factor influencing students’ academic and emotional experiences in language learning. However, previous studies have often examined teacher–student relationships, engagement, and enjoyment separately, with limited attention to the perspectives of both teachers and students. Therefore, this study explored teachers’ and students’ perceptions of teacher–student relationships in English classes and investigated how these relationships influence students’ learning engagement and enjoyment. A qualitative case study was conducted at a public junior high school in Bali, Indonesia, involving two English teachers and approximately 70 eighth-grade students. Data were collected through open-ended questionnaires, semi-structured interviews, and classroom observations, and analyzed using thematic analysis with methodological triangulation to enhance trustworthiness. The findings revealed that teachers viewed positive teacher–student relationships as being built through supportive interactions, constructive conflict management, and emotional connection. Students associated positive relationships with supportive teacher attitudes, effective communication, engaging classroom activities, and a comfortable learning environment. Overall, positive teacher–student relationships promoted students’ participation, confidence, engagement, and enjoyment in English learning by creating supportive and meaningful classroom experiences. These findings highlight the multidimensional nature of teacher–student relationships and emphasize their importance in fostering effective EFL teaching and learning.for improving the quality and sustainability of inclusive English education for deaf learners.